KONSTRUKSI TUBUH DALAM CERITA PENDEK KERONCONG PEMBUNUHAN KARYA SENO GUMIRA AJIDARMA - Uci Elly Kholidah (Kantor Bahasa Provinsi Gorontalo, 2017)
This study attempts to break down the construction of body which is consiston short story entitled Keroncong Pembunuhan by Seno Gumira Ajidarmaby using postcolonial body proposed by Sara Upstone. Method of the studyis deconstructive reading method. The result of this study shows that in thisshort story, Seno Gumira Ajidarma does not totally reject solid space butstill serves the magical and metaphor space simultaneously.